The Vulcan 10 PW project - Hernandez-Gomez, C; Blake, S; Chekhlov, O; Clarke, R; Dunne, A; Galimberti, M; Hancock, S; Heathcote, R; Holligan, P; Lyachev, A; Matousek, P; Musgrave, I; et al. (2010)
The aim of this project is to establish a 10 PW facility on the Vulcan laser system capable of being focussed to intensities of at least 10 Wcm and integrate this into a flexible and unique user facility This paper will present progress made in Phase one developing the 10PW Front End as well as the concept for the new Vulcan 10 PW facility. The new facility will be configured in a unique way to maximise the scientific opportunities presented through a combination with the existing capabilities already established on Vulcan. This ground breaking development will open up a range of new scientific opportunities. © 2010 IOP Publishing Ltd.